Baire space in neutrosophic 𝛍-topological spaces - Nirmal Sarkar; Ashoke Das; Towhid Aman (Journal of Fuzzy Extension and Applications)
In this article, we introduce and discuss the concepts of neutrosophic µ-dense, neutrosophic µ-nowhere dense, and neutrosophic µ-first category sets. We also define and characterize the concept of neutrosophic µ-baire space. Moreover, we investigate neutrosophic (µ, η)-continuity and neutrosophic (µ, η)-open functions and establish some results on the preservation of neutrosophic µ-baire space under such functions.